Immunohistological Localization of BMP-2, BMP-7, and Their Receptors in Knee Joints with Focal Cartilage Lesions. (3rd January 2012) - Schmal, Hagen; Mehlhorn, Alexander T.; Pilz, Ingo H.; Dovi-Akue, David; Kirchhoff, Christina; Südkamp, Norbert P.; Gerlach, Ulrike; Lohrmann, Christian; Niemeyer, Philipp
Abstract : Introduction . Although it is well known that BMP-2 and BMP-7 play significant roles in cartilage metabolism, data about intra-articular expression and localization of these proteins and their receptors in humans are rare. Methods . Biopsies of synovia and debrided cartilage were taken in patients undergoing autologous chondrocyte implantation. Expression of BMP-2, BMP-7, and their receptors BMPR-1A, BMPR-1B and BMPR-2 were semiquantitatively evaluated by immunohistological staining. Results . BMP-7 was equally highly expressed in all cartilage and synovial biopsies. Increased levels of BMPR-1A, but not of BMPR-1B, and BMPR-2, were found in all synovial and 47% of all cartilage samples (P = 0.002 ). BMP-2 was positively scored in 47% of all cartilage and 40% of all synovial specimens. Defect size, KOSS, Henderson or Kellgren-Lawrence score did not statistically significant correlate with the expression of the analyzed proteins or Mankin and Pritzker scores. Duration of symptoms and localization of lesions were associated with KOSS (P < 0.02 ), but there was no influence of these parameters on protein expression. Conclusions . BMP-2, BMP-7, and BMPR-1A were expressed in cartilage and synovia of knees with focal cartilage lesions. Although defect localization and duration of symptoms decisively influence KOSS, there was no associated alteration of protein expression observed.